Effects of Acupuncture at St36 on Pharmacokinetics of Schisandra lignans in rats. Issue 3 (June 2015) - Ji, De; Ning, Ziwan; Mao, Chunqin; Sun, Yong; Liu, Jing; Ji, Lin; Yang, Huan; Huang, Zhi-Jun; Lu, Tulin
Objective: To investigate the influence of acupuncture at ST36 on the pharmacokinetics of Schisandra lignans including schisandrin, deoxyschisandrin and schisandrin B after intragastric administration of Schisandra chinensis (SC) in rats. Methods: Twelve male Sprague-Dawley rats were randomly divided into two study groups: SC and SC+acupuncture. Rats in both groups received intragastric SC extract at 5.0 g/kg. Rats in the SC+acupuncture group additionally received acupuncture stimulation at ST36 for 30 min after SC administration. Acupuncture needles were rotated bilaterally for 1 min, left in situ for 20 min, then electrically stimulated for 10 min at 50 Hz frequency and 1–3 mA intensity. A sensitive and specific high performance liquid chromatography electrospray tandem mass spectrometry procedure was developed and validated for simultaneous analysis of three bioactive lignans (schisandrin, deoxyschisandrin and schisandrin B) in rat plasma. Results: There were significant differences (p<0.05) between the two study groups in various pharmacokinetic parameters. Area under the plasma concentration–time curve (AUC0–t ), area under the plasma concentration–time curve to time infinity (AUC0–∞ ) and peak plasma concentration (Cmax ) for schisandrin, absorption half-life (T1/2α ) and AUC0–t for deoxyschisandrin, and Cmax for schisandrin B were increased in the SC+acupuncture group compared with the SC group. T1/2α for schisandrin B only and time to peak concentration (Tmax ) for all three lignans were reduced following acupuncture. Conclusions: Acupuncture stimulation at ST36 affects the pharmacokinetics of SC in rats. Acupuncture may have a beneficial role in promoting the absorption of lignans from extracts of SC.